Multidomain Determinants of Stunting in Six High-Prevalence Districts in Sulawesi, Indonesia: A Cross-Sectional Analysis of the 2024 Indonesian Nutritional Status Survey - Yessy Kurniati; Nazihah Mukhtar (Direktorat Politeknik Kesehatan Makassar, 2026)
Stunting remains a major public health challenge, particularly in areas characterized by socioeconomic and environmental disparities. Although the prevalence of stunting in Indonesia declined to 19.8% in 2024, several districts in Sulawesi continue to report substantially higher rates. This study aimed to identify family, nutrition-sensitive, and nutrition-specific determinants of stunting across six high-prevalence districts in Sulawesi, Indonesia. A cross-sectional study was conducted using secondary data from the 2024 Indonesian Nutritional Status Survey (SSGI). The study included 3,263 households with children under five years of age from Mamuju (n=552), Gorontalo City (n=561), Buton Selatan (n=580), Minahasa Selatan (n=480), Jeneponto (n=580), and Buol (n=510). Data were analyzed using descriptive statistics, bivariate analysis, and multivariate logistic regression. Multivariate analysis revealed substantial district-level variation in the determinants of stunting. In Mamuju, proper kitchen wastewater disposal systems were associated with lower odds of stunting (AOR=0.36; 95% CI: 0.181–0.706; p=0.003). In Buton Selatan, incomplete hepatitis immunization increased the odds of stunting (AOR=1.88; 95% CI: 1.036–3.401; p=0.038). In Buol, higher maternal education was associated with lower odds of stunting (AOR=0.71; 95% CI: 0.524–0.969; p=0.031). In Minahasa Selatan, higher paternal education (AOR=0.56; 95% CI: 0.338–0.932; p=0.026) and health insurance ownership (AOR=0.43; 95% CI: 0.208–0.891; p=0.023) were protective factors. An association between paternal employment and stunting was also observed, although this finding should be interpreted cautiously because of the small subgroup size. No significant determinants were identified in Gorontalo City or Jeneponto. Determinants of stunting varied across districts, indicating that stunting is highly context-dependent. District-specific interventions focusing on sanitation, immunization coverage, parental education, and socioeconomic support are needed to accelerate stunting reduction in high-prevalence areas.